ANALISIS PENDAPATAN DAN PENGAMBILAN KEPUTUSAN DALAM MENENTUKAN TANAMAN SAYURAN UNGGULAN DI KECAMATAN GISTING KABUPATEN TANGGAMUS - Khoirunnisa, Atika; Haryono, Dwi; Nugraha, Adia (Jurnal Ilmu-Ilmu Agribisnis, 2013)
This study aims to: (1) analyze farm income of each type of vegetable crops (green cabbage, eggplant, tomatoes, cucumbers, and chilli), (2) arrange the sequence of the competitive vegetables as the farming improvement efforts during the process of agricultural activity, (3) analyze the relation between the farm income and the result of the decision-making of competitive vegetable. This research was conducted in two villages, namely Campang Village and Gisting Atas Village of Gisting Subdistrict of Tanggamus Regency.Â  The two vilages of this research were chosen on purpose for they were center of highland vegetable in Lampung. The number of 52 vegetable farmers were selected for determining the income from vegetable crops.Â  In addition, 22 respondents of experts in development of vegetable crops were selected for determining the priority of vegetables. The method of analysis used in this study was income analysis and Analytical Hierarchy Process method. The results showed that: (1) total income of the vegetable crops in Gisting Subdistrict of Tanggamus Regency per hectare of chilli was Rp97,097,436, green cabbages Rp27,801,568, eggplant Rp26,972,266, tomatoes Rp16,529,97 and cucumber Rp9,280,180, (2) the right orders of the competitive vegetable for farming improvement efforts during the process of agricultural activity were chilli, green cabbages, tomatoes, eggplants, and cucumbers, (3) there wasÂ  positive and close relationship between income and decision making, in which the greater the income of a commodity, the more powerful of the farmerâs decision making to choose the commodity. Keywords:Â  competitive vegetable,Â  commodity, decision making, income